(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Online customer reviews, online customer ratings, and content marketing are aspects that are thought to influence buying interest. The purpose of this study was to determine the effect of online customer reviews, online customer ratings, and content marketing on buying interest on the Shopee Marketplace. This research is in Denpasar City and the research population is all residents of Denpasar City who have shopped on the Shopee e-commerce site/application. Completion of the number of samples was carried out using the slovin formula so that the number of samples was set at 100 people. The sampling technique used is purposive sampling. Data collection was carried out using a questionnaire method. To test the hypothesis carried out by using multiple linear regression analysis, coefficient of determination, t test and F test. From the results of the analysis it can be concluded that: 1) online customer reviews have a positive and significant effect on purchase intention, 2) online customer ratings have a positive and significant effect on purchase intention, 3) content marketing has a positive and significant effect on purchase intention, 4) online customer reviews, online customer ratings and content marketing have a positive and significant effect on purchase intention.